Current Advances in γδ T Cell-Based Tumor Immunotherapy - Lo Presti, Elena; Pizzolato, Gabriele; Gulotta, Eliana; Cocorullo, Gianfranco; Gulotta, Gaspare; Dieli, Francesco; Meraviglia, Serena (Frontiers in Immunology, 2017)
γδ T cells are a minor population (∼5%) of CD3 T cells in the peripheral blood, but abound in other anatomic sites such as the intestine or the skin. There are two major subsets of γδ T cells: those that express Vδ1 gene, paired with different Vγ elements, abound in the intestine and the skin, and recognize the MHC class I-related molecules MICA, MICB and ULBPs expressed on many stressed and tumor cells. Conversely, γδ T cells expressing the Vδ2 gene paired with the Vγ9 chain, are the predominant (50% to 90%) γδ T cell population in the peripheral blood and recognize phosphoantigens (PAgs) derived from the mevalonate pathway of mammalian cells, which is highly active upon infection or tumor transformation. Aminobisphosphonates (n-BPs), which inhibit farnesyl pyrophosphate synthase, a downstream enzyme of the mevalonate pathway, cause accumulation of upstream PAgs and therefore promote γδ T cell activation. γδ T cells have distinctive features that justify their utilization in anti-tumor immunotherapy: they do not require MHC restriction and are less dependent that αβ T cells on co-stimulatory signals, produce cytokines with known anti-tumor effects as IFN-γ and TNF-α and display cytotoxic and anti-tumor activities in vitro and in mouse models in vivo. Thus, there is interest in the potential application of γδ T cells in tumor immunotherapy and several small-sized clinical trials have been conducted of γδ T cell-based immunotherapy in different types of cancer after the application of PAgs or n-BPs plus IL-2 in vivo or after adoptive transfer of ex vivo expanded γδ T cells, particularly the Vγ9Vδ2 subset. Results from clinical trials testing the efficacy of any of these two strategies have shown that γδ T cell-based therapy is safe, but long-term clinical results to date are inconsistent. In this review we will discuss the major achievements and pitfalls of the γδ T cell-based immunotherapy of cancer.